The relationship between match statistics and top 100 ranking in professional men's tennis - Reid, M.; McMurtrie, D.; Crespo, M. (International Journal of Performance Analysis in Sport, 2010)
Match statistics are supplied at the majority of professional tennis tour events. The governing body of the men's tour - the Association of Tennis Professionals (ATP) - updates players' statistical profiles on a weekly basis. The relationships between the rankings and fourteen statistics describing the match performance of the top 100 male professional players in 2007 were examined to determine which statistics were most related to playing success. Partial correlations determined the strength of these associations and selected variables were entered into a stepwise regression procedure to predict professional ranking. Five variables were significant predictors of top 100 ranking while only second serve return points won and second serve points won remained in the final prediction equation, which accounted for 52% of the variance in professional ranking: predicted men's professional ranking = 548.5 + -666.6 * second serve points won + -319.9 * second serve return points won. This analysis suggests that second serve points won and second serve return points are among the most relevant statistics commonly available to ATP players.